Post operative nausea and vomiting, its causes, and the way of its prevention and treatment - Maharjan, Surendra; Bing, Zhang (Birat Journal of Health Sciences, 2021)
Postoperative nausea and vomiting is still occurring in one third of the patient undergoing surgery under general anaesthesia even after following the guidelines and using multi modal approach for its prevention. Lots of studies have been done for its prevention but very few studies are done for its treatment in Post anaesthetic care unit after the failure of prophylaxis. The purpose of this article is to know about the risk factor, incidence of nausea and vomiting after surgery, its mechanism, available medication (pharmacological and nonpharmacological), reducing risk factor, and mainly to know about the method of using the antiemetic medication in PACU after the failure of the prophylactic medication.